Intervensi untuk Mengurangi Stigma pada Penderita Skizofrenia - Ina Dewi Ardiyani; Hanafi Muljohardjono (Jurnal Psikiatri Surabaya, 2020)
Schizophrenia is one of the mental disorders with severe and persistent manifestations of psychosis symptomps chronically in which do not treated properly because of stigmatized in society, as well as the impact of stigma in schizophrenia that cause inhibition of recovery, interpersonal relationship, and socializing, then creates poor quality of life. There are several strategies of intervention used to reduce stigma which can be applied and adapted for Indonesia with accompanying considerations and challenges with different targets and goals to be achieved.